Beyond oncology: Selinexor’s journey into anti-inflammatory treatment and long-term management - Li, Dan; Fang, Hong; Zhang, Rong; Xie, Qian; Yang, Yang; Chen, Lin (Frontiers in Immunology, 2024)
Selinexor, a selective inhibitor of nuclear export (SINE), is gaining recognition beyond oncology for its potential in anti-inflammatory therapy. This review elucidates Selinexor's dual action, highlighting its anti-tumor efficacy in various cancers including hematologic malignancies and solid tumors, and its promising anti-inflammatory effects. In cancer treatment, Selinexor has demonstrated benefits as monotherapy and in combination with other therapeutics, particularly in drug-resistant cases. Its role in enhancing the effectiveness of bone marrow transplants has also been noted. Importantly, the drug's impact on key inflammatory pathways provides a new avenue for the management of conditions like sepsis, viral infections including COVID-19, and chronic inflammatory diseases such as Duchenne Muscular Dystrophy and Parkinson's Disease. The review emphasizes the criticality of managing Selinexor's side effects through diligent dose optimization and patient monitoring. Given the complexities of its broader applications, extensive research is called upon to validate Selinexor's long-term safety and effectiveness, with a keen focus on its integration into clinical practice for a diverse spectrum of disorders.